A MODEL OF THE INFLUENCES OF A FOREST FIRE ON ITS NEIGHBORHOODS AND RELATED RISK MANAGEMENT ASPECTS - POSEA, Valentin (Annals of Spiru Haret University. Economic Series, 2017)
Abstract. The aim of the present paper is to produce a model for the propagation of a forest fire analyzing the influences that the fire zone has on its neighborhoods. The model is aMoore cellular automaton type. It depends on six parameters: the medium slope of the elementary cell, the layer type, and the burning time of the fuel, the fuel type, the wind direction and speed. In order to study the influences of various parameter configurations on the system of vicinities of a fire cell we construct some special directional correlation functions. An application is elaborated based on real data.